The decline of deer hunting: Demographic analysis and future projections of Wisconsin deer hunters - Adam S. Mohr; Meghan E. Henry; Beth Wojcik; Christine Anhalt‐Depies; Daniel J. Storm (Wildlife Society Bulletin)
Abstract The number of hunters in the United States has been declining in recent decades, raising concerns about the loss of hunting‐generated funds for conservation and management. We used demographic models to examine the relative effects of time period, age, birth cohort, and gender on Wisconsin, USA residents' likelihood to purchase a deer hunting license, and we used these models to create estimated projections of the number of deer hunters out to 2040. In each projection scenario we examined, the number of male deer hunters declined at a rate of −2.2% to −1.5% per year, and the decline was attributable to declining participation rates across the entire hunter population. For female deer hunters, projections were inconsistent about whether the population would grow or remain stable near current levels. The rapidity and sustained duration of deer hunter declines will see deer populations outstrip the diminishing management capacity of recreational hunting and reduce funding for conservation and management programs.